ChemInform Abstract: Enantio‐ and Diastereoselective Vinylogous Mukaiyama Aldol Reactions of α‐Keto Phosphonates with 2‐(Trimethylsilyloxy)furan Catalyzed by Bis(oxazoline)‐Copper Complexes. Issue 30 (4th July 2013) - Hou, Gang; Yu, Jipan; Yu, Chengbin; Wu, Guiping; Miao, Zhiwei
Abstract The present method is suitable for functionalized α‐keto phosphonates (II) and allows the synthesis of α‐hydroxy phosphonates (III) bearing two chiral centers in high yields as well as high enantioselectivities.